Recuerdo De Huautla: An Odyssey of Inner Space - Peacock, Andrew G. (Culture, 1981)
The contemporary literature on social change in Latin America reflects a perception of folk and modern systems as incompatible, even antagonistic entities. Consistent with this view, change in Indian communities is seen as following one of two basic forms; towards (i) assimilation into the national political, economic and social systems, or (ii) the development of isolationist subcultures. This paper explores the process by which communities, and consequently the individuals thereof, become characterized as traditional and conservative with respect to development. The varied, often opposing views of Indian reaction to change suggest a need for reviewing the analytical categories considered to be diagnostic of traditionalism.